Analysis OF Work Readiness Students Universitas PGRI Semarang - M Rofi; Efriyani Sumastuti; Qristin Violinda (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
"What effect does the use of information technology have?" was the goal of this research., self-efficacy, career planning, career flexibility, and career maturity on students at Universitas PGRI Semarang who were prepared for the workforce. With a total sample size of 365, the study's objects were undergraduate students from the UPGRIS classes of 2019 and 2020. employing a sample random sampling approach in research methodologies utilising probability sampling techniques. Multiple linear regression analysis, R2 (coefficient determination), the classical assumption test, and hypothesis testing were performed using SPSS 22.00 in this study. With an adjusted R square value of 0.61%, the findings demonstrated that information technology use (0.000), self-efficacy (0.013), career planning (0.000), and career maturity (0.000) all had an effect on work readiness. This suggests that it can explain 61% of the work readiness variable, with variables not included in this research explaining the remaining 39%..